The effect of hyperglycemia and troponin I levels on the prognosis of acute ischemic stroke in non-diabetic and diabetic patients - Hidayati Lubis, B. Ag.; Anwar, Yuneldi; Arina, Cut Aria (International Journal of Research in Medical Sciences, 2019)
Background: Acute hyperglycaemia may predict a higher risk of hospitalization mortality after ischemic stroke in non-diabetic patients and a higher risk of poor functional improvement in non-diabetic stroke patients. It is thought that insula involvement in right cerebral hemispheres has a role in autonomic control of the heart. Troponin is a sensitive marker that is widely used in the diagnosis and risk stratification of acute coronary syndrome. High troponin I is found in acute stroke patients and is associated with a poorer prognosis. Methods: The study was cross-sectional, 30 patients diagnosed with acute ischemic stroke at Haji Adam Malik General Hospital Medan from June 16, 2017 to March 31, 2018. All participants were taken blood to measure blood glucose levels at the time of admission >140 mg/dL with a history of previous or not diabetes. Troponin I levels was checked when acute ischemic stroke patients had entered the inpatient room. The patient’s prognosis is determined by National Institute of Health Stroke Scale (NIHSS) and Modified Rankin Scale (MRS). The calculation of NIHSS and MRS scores was performed on the first day of admission and the fourteenth day after being admitted to the hospital. Statistical test using Fisher exact test. Results: Of the 30 samples consisted of 19 men and 11 women. The significant effect between hyperglycaemia in acute ischemic stroke patients with diabetes and non-diabetes on the fourteenth day NIHSS (PR 2.8; 95% CI, 1.184-6,622; p=0.045). Conclusions: There was an effect between hyperglycaemia in non-diabetic and diabetic on the poor prognosis of acute ischemic stroke patients.